EFFECT OF ADIPOSITY AND FAT DISTRIBUTION ON ENDOMETRIAL CANCER RISK IN POSTMENOPAUSAL PATIENTS - Papestiev, Irena Aleksioska; Antovska, Vesna; Dabeski, Drage; Ilieva, Natasha; Kjaev, Ivo; Markova, Ana Daneva; Dzikova, Elena; Asani, Pajtim (Journal of Morphological Sciences; Vol 6 No 2 (2023): JMS, 2023)
Endometrial cancer (EC ) is the fourth most common cancer in women worldwide, with rising incidence partly due to changing reproductive trends and ever increasing obesity. Obesity, especially central adiposity, is linked with endometrial adenocarcinoma, possibly due to elevated estrogen and decreased sex hormone-binding globulin levels. The study aims to evaluate the impact of obesity on endometrial malignancy and to determine whether central adiposity (measured by the waist-to-hip circumference ratio) serves as a better indicator of endometrial cancer risk than BMI. In this cross-sectional study, we studied 164 postmenopausal patients from the University Clinic of Obstetrics and Gynaecology in Skopje. Patients were admitted to the hospital for histopathological examination of endometrial layer because of vaginal bleeding with endometrial thickness >4mm, or other sonographic endometrial abnormalities. Histopathological findings subdivided them into two categories: with malignancy (group I) or benign abnormality (group II). Standard examinations and measurements, including BMI and waist-to-hip ratio, were performed. A significant association was observed between endometrial malignancy and obesity as measured by waist-to-hip ratio. In the distribution of data related to BMI and histopathological findings from the endometrial biopsy for Pearson Chi-square=8.35 and p<0.01(p=0.004) there is a significant difference. For Odds Ratio=2.71 (95.%CI:1.36-5.38), patients who had a  BMI â‰¥ 30 kg/m2 were 2.71 times more likely to have endometrial malignancy than patients who had a BMI <30 kg/m2, (p<0.01). There is a significant difference in the shown distribution of data related to waist circumference/hip circumference and histopathological findings of endometrial sampling Pearson Chi-square=79.22 and p<0.001(p=0.000). For Odds Ratio=40.89 (95.% CI:15.23-109.78), patients who had waist circumference/hip circumference â‰¥ 0.85 were 40.89 times more likely to have endometrial malignancy than patients who had waist circumference/hip circumference <0.85, (p<0.001). Upon analysing the contribution of central obesity determined by waist-to-hip ratio, it was found to have a more substantial impact (Wald = 37.76, p < 0.001) compared to BMI (Wald = 0.97, p= 0,32). Our study confirms that obesity is a risk factor for endometrial malignancy. Furthermore, fat distribution proves to be a more crucial and accurate indicator of endometrial cancer risk than overall obesity. The statistical significance of the waist circumference to hip circumference ratio exceeded that of BMI. Therefore, even if a patient has a normal BMI, but a waist-to-hip circumference ratio greater than 0,80, she should be considered at increased risk for endometrial malignancy and should be closely monitored in the future in order to detect any malignant changes. Key words: endometrial cancer, body mass index, waist circumference - hip circumference ratio, obesity.